Analisis Penatausahaan dan Penyusunan Laporan Pertanggungjawaban Bendahara Serta Penyampaiannya Pada Badan Pengelolaan Keuangan Daerah Kabupaten Solok Selatan - Dona, Sepria; Yenti, Elfina (Jurnal Akuntansi Syariah (JAkSya), 2021)
The problem of this research is how the administration and preparation of the Treasurer's Accountability Report and its submission to the Regional Financial Management Agency of South Solok Regency. The purpose of this study was to determine: Administration and preparation of the Accountability Report of the Revenue Treasurer at the Regional Financial Management Agency of South Solok Regency; Administration and preparation of the Expenditure Treasurer accountability report at the Regional Financial Management Agency of South Solok Regency. The research method used is descriptive qualitative and the subject of this research is the Revenue Treasurer and the Expenditure Treasurer of the Regional Financial Management Agency of South Solok Regency. Data collection techniques used are interviews, observation and documentation of research subjects. While the data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of this study indicate that: (1) the receipt treasurer of the Regional Financial Management Agency of South Solok Regency has implemented administration and preparation of accountability reports in accordance with applicable guidelines, from the initial stage of collecting transaction evidence to the stage of ratification and submission to related parties. ; (2) the expenditure treasurer of the Regional Financial Management Agency of South Solok Regency has implemented the administration and preparation of the accountability report in accordance with the applicable guidelines from the expenditure accounting stage to the description of the overall procedure for delivering accountability.